2016
DOI: 10.2967/jnumed.115.163766
|View full text |Cite
|
Sign up to set email alerts
|

The Incremental Value of Subjective and Quantitative Assessment of 18F-FDG PET for the Prediction of Pathologic Complete Response to Preoperative Chemoradiotherapy in Esophageal Cancer

Abstract: A reliable prediction of a pathologic complete response (pathCR) to chemoradiotherapy before surgery for esophageal cancer would enable investigators to study the feasibility and outcome of an organ-preserving strategy after chemoradiotherapy. So far no clinical parameters or diagnostic studies are able to accurately predict which patients will achieve a pathCR. The aim of this study was to determine whether subjective and quantitative assessment of baseline and postchemoradiation 18 F-FDG PET can improve the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(131 citation statements)
references
References 45 publications
2
129
0
Order By: Relevance
“…Although a number of studies have included only between 20 and 70 patients [50, 71, 8692], some of the most recent studies have included between 80 and more than 200 patients: 88 patients with oropharyngeal squamous cell carcinoma [93], 103 with bone and soft tissue lesions [94], 101 with early-stage NSCLC [95], 112 with oesophageal cancer and 101 with NSCLC [60], 113 with glioma [36], 107 and 217 with oesophageal cancer [96, 97], 132 with lymph node involvement in lung cancer [98], 116, 195 and 201 with NSCLC [99101], 137 with pancreatic lesions [102], and 188 lesions in lymphoma patients [103]. Some of the most recent studies have also used more robust statistical analysis, compared to these recently reviewed [28], several of them using a machine-learning method, e.g.…”
Section: Promising Clinical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of studies have included only between 20 and 70 patients [50, 71, 8692], some of the most recent studies have included between 80 and more than 200 patients: 88 patients with oropharyngeal squamous cell carcinoma [93], 103 with bone and soft tissue lesions [94], 101 with early-stage NSCLC [95], 112 with oesophageal cancer and 101 with NSCLC [60], 113 with glioma [36], 107 and 217 with oesophageal cancer [96, 97], 132 with lymph node involvement in lung cancer [98], 116, 195 and 201 with NSCLC [99101], 137 with pancreatic lesions [102], and 188 lesions in lymphoma patients [103]. Some of the most recent studies have also used more robust statistical analysis, compared to these recently reviewed [28], several of them using a machine-learning method, e.g.…”
Section: Promising Clinical Resultsmentioning
confidence: 99%
“…neural networks [96], support vector machines [94, 98, 103] or the least absolute shrinkage and selection operator (LASSO) [95, 101]. The majority of these recent studies have concluded that TA can provide useful quantitative metrics regarding patient management (prognosis, response to therapy, distant metastasis prediction) in different cancer models except one that showed more mixed results [104], whereas another concluded that the improvement, although significant, may not be sufficient to have a clinical impact [97]. …”
Section: Promising Clinical Resultsmentioning
confidence: 99%
“…An initial study by Tan et al found in 20 patients that 2 SUV mean parameters, SUV mean decline and SUV mean skewness, and 3 texture features GLCM inertia, GLCM correlation, and GLCM cluster prominence, were significant predictors of complete response with an AUROC of 0.76 [31]. In 217 patients with adenocarcinoma, Van Rossum et al developed a prediction model which included change in run length matrix (RLM) run percentage, change in GLCM entropy, and post-chemoradiation roundness, and increased the corrected c-index (concordance-index, comparable to AUROC) from 0.67 to 0.77, compared to the clinical model alone [32]. Yip et al found that a change in run length and size-zone matrix differentiated responders from non-responders [33].…”
Section: F-fdg Pet Radiomicsmentioning
confidence: 99%
“…Not every radiomic feature that significantly predicted the survival of lung cancer patients could also predict the survival of head-and-neck cancer patients and vice versa. Radiomic features are better at predicting treatment response than conventional measures, such as tumor volume and diameter, and the maximum radiotracer uptake on positron emission tomography (PET) imaging [19][20][21][22][23][24][25]. Metastatic latency of tumors could also be predicted by radiomic features [26][27].…”
Section: Discussionmentioning
confidence: 86%